Maskulinitas Hegemonik Dalam Novel Natisha Persembahan Terakhir Karya Khrisna Pabichara - Yusuf, Fatimah (ANTHOR: Education and Learning Journal, 2023)
Talking about masculinity means examining the ideas, norms and structures formed in social lives. Masculinity does not have a fixed form and applies the same in every region, but is closely linked to the patriarchal system which prioritizes domination over a particular gender. Hegemonic masculinity is the practice of how to be a man who conforms to standards and then becomes a role model for others in order to maintain hierarchical integrity. This research examines how hegemonic masculinity develops in the novel Natisha Persembahan Terakhir by Khrisna Pabichara. Using the lens of hegemonic masculinity in the style of R. W. Connell, three types of hegemonic masculinity are found embedded in the male characters or characters in the novel. First, fighting muscle power or fighting is a manifestation of a man's courage and on the other hand, is an expression of shame. Second, men are still never satisfied even though they have achieved success in the form of a spouse, children or property. Third, hegemonic masculinity is related to violence or domination of women's bodies. Characters who practice masculinity actually become victims of the absurd criteria of being men because they still experience losses from psychological and physical aspects.